The Impact of Digital Technologies on Formative Assessment and the Learning Experience - Anastasopoulou, Eleni; Konstantina, Gkika; Tsagri, Angeliki; Schoina, Ioanna; Travlou, Chrysi; Mitroyanni, Evangelia; Lyrintzi, Theofania (Technium Education and Humanities, 2024)
The integration of digital technologies into formative assessment has revolutionized modern education by enhancing the learning experience and transforming how educators evaluate student progress. Digital tools such as Learning Management Systems, Artificial Intelligence-driven platforms, and immersive technologies like Virtual Reality (VR) and Augmented Reality (AR) provide real-time feedback, personalized learning pathways, and increased engagement. These innovations support diverse learning styles and foster deeper understanding through interactive and multimedia-rich environments. However, challenges such as the digital divide, lack of teacher training, ethical concerns surrounding data privacy, and biases in AI-driven systems pose significant barriers to equitable implementation. Future trends, including predictive analytics, blockchain for secure data management, and gamified assessment strategies, offer promising avenues for further development. Addressing these challenges while leveraging technological advancements can lead to a more inclusive, engaging, and effective educational landscape, preparing students for the demands of a rapidly evolving world.